HUBUNGAN DAYA TAHAN KECEPATAN TERHADAP HASIL LARI 400 METER PADA ATLET ATLETIK PUTRA PERSATUAN ATLETIK SELURUH INDONESIA (PASI) RIAU - Septiandi Eka Putra; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This problem aims to prove whether the correlation between the speed endurance and the result of the men’s 400 meter athletich athletes running test in athlethics assocation of indonesia (PASI) Riau. The forms of this research are correlation research, the population in this research from the 400 meters sprinter athletich athletes in athletics association of indonesia (PASI) Riau. The sample in this research is the 400 meters sprinter athletich athletes assocation of indonesia (PASI) Riau, which have numbered 6 people. The first analysis in the calculation of the correlation between X and Y, where rtab at significantet level α (0,05) = 0,950 means rresult (0,392) < rtable (0,950), which means the hypothesis rejected and thre is no significant correlation betwen endurance speed and the result of 400 meters men’s running test in athlethics assocation of indonesia (PASI) Riau. Then it can by concluded that correlation betwen x and y or the correlation between endurance speed with result of 400 meter running test are weak.Key Words: speed endurance and running sprint 400 meters